Remittances and Sociodemographic Vulnerability in Middle Low-Incomes Households in Cali - Roa Martínez, María Gertrudis (Sociedad y Economía, 2012)
The consumption of remittances can be related to socio-demographic structures that reveal social vulnerability such as high rates of demographic and economic dependency. This article describes the socio-demographic and economic characteristics of households located in layers two and three of Cali (middle low-income), according to the destination that give the remittances. The results show that poorer households are usually characterized by the use of remittances in basic needs like food, house rent and utility payments. Consumption on health and education are related with high rates of childhood and aging. Households that spend the remittance for investment and leisure finance the basic needs from their own income.